Fulfillment of workers’ rights in remote working: the perspective of labor development principle in Indonesia - Hidayah, Nur Putri; Anggraeny, Isdian (Faculty of Law, University of Muhammadiyah Malang, 2023)
The popularity of working from home or remote working is rising globally. In Indonesia, the existence of the internet underpins the trend of working from home since accessing this technology is effortless. However, existing regulatory provisions mostly govern matters regarding office work, while the rights and responsibilities between employers and employees in the remote working scheme have never been specifically regulated. This situation creates a huge gap between what is stated in a written law and law in action. This research aims to analyze the congruence of agreements with the fulfilment of rights of workers working from home from the perspective of legislation and the principles of labor development. This research employed sociological and legal methods. The research results indicate that the fulfilment of labors’ rights in both the agreement and implementation has not met the principles of labor development. The conflict of rights and criminal violations regarding this matter is obvious since workers’ rights governed in the legislation are not governed in the work agreement. Moreover, there is still incongruence between the regulations and implementation of the rights of workers regarding the portion of break/leave and overtime wages.